PERANCANGAN ABSENSI QR CODE MAHASISWA BERBASIS WEBSITE PADA STIKOM TUNAS BANGSA PEMATANG SIANTAR MENGGUNAKAN METODE AGILE - Rafai, Muhammad; Solikhun, Solikhun; Safii, M. (Jurnal Manajamen Informatika Jayakarta, 2024)
This research discusses the implementation of a web-based attendance system that utilizes QR scanner technology to record individual attendance, especially in an educational environment. The report also highlights the primary benefits of this approach, such as process efficiency, data accuracy, and real-time information access. The web-based attendance system using QR scanner technology not only enhances administrative effectiveness but also provides a more modern and interactive experience for individuals who need to be accounted for. This helps reduce the risk of errors in manual attendance recording and provides faster and more accurate access to attendance data. In this research, the author used various methods to collect data, including observation and a literature review. The author relied on various online documentation sources as data references for this report. The documents used by the author included several Scopus-indexed journals, e-books, and various digital news pages from the past 5 years. For the development method of this website, the author employed the Agile methodology. Agile is one of the models of the Software Development Life Cycle (SDLC). The results of this research, which combine QR codes and web access, make this attendance system a relevant and innovative solution for efficient attendance management.